Rational expectation of all company is to gain maximum profit, as Wirontono Baru Company do. It is a company which is expert in a shrimp freezing. In its output, the company is facing an obstacle i.e. raw material avaibility, job shift employee, coldstorage capacity and freezing machine capacity. Nevertheless, maximum profit is still primary purpose achieved by a company. Optimalization shows that production is not reaching an optimal condition yet. This is shown by a differences between actual - Iis Diatin; Narni Farmayanti; Selly Sefrina (Buletin Ekonomi Perikanan, 2006)
Rational expectation of all company is to gain maximum profit, as Wirontono Baru Company do. It is a company which is expert in a shrimp freezing. In its output, the company is facing an obstacle i.e. raw material avaibility, job shift employee, coldstorage capacity and freezing machine capacity. Nevertheless, maximum profit is still primary purpose achieved by a company. Optimalization shows that production is not reaching an optimal condition yet. This is shown by a differences between actual profit and optimalization result profit. If company produces with an optimum combination of result, then it will get an addition profit as Rp 2.633.481.200,00. This dual analysis shows that several resources is not used yet, optimally. Sensitivity of analysis shown that range of optimality of destination function and right hand side range are wide.